2014
DOI: 10.1177/1748048514548534
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous sources hurt credibility of news stories across cultures: A comparative experiment in America and China

Abstract: This cross-cultural experiment ( N = 620) tested the impact of the use of anonymous sources on perceived news story credibility in America and China, two countries with assumed different journalistic standards. Both Americans and Chinese rated news stories with only anonymous sources as less credible than stories with identified sources. The attitude of Americans towards news stories was found to be more positive. The study represents the first comparative research on the topic with rigorously established cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Mass media exert a significant effect on spreading and seeking health information [31], and they play an important role in early diagnoses and disease management [32]. In consideration of the decrease in the credibility of media campaigns [33, 34], patients with a prevention focus are less likely to use mass media than those with a promotion focus. Emerging treatment-related health information is mainly disseminated to the public through mass media.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Mass media exert a significant effect on spreading and seeking health information [31], and they play an important role in early diagnoses and disease management [32]. In consideration of the decrease in the credibility of media campaigns [33, 34], patients with a prevention focus are less likely to use mass media than those with a promotion focus. Emerging treatment-related health information is mainly disseminated to the public through mass media.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Pakistan media may have in their political reports given reasons for sources seeking anonymity to convince the audience about the fear such sources faced in being identified and also to boost media credibility in the eyes of the audience. Pjesivac and Rui (2014) found that news audience based out of the United States and China considered news based only on anonymous sources as less credible than stories where journalists identified their sources. This may be a pointer to enhanced journalistic credibility if anonymous sources are identified as much as possible in news reports.…”
Section: Discussionmentioning
confidence: 98%
“…A study of news reports that appeared in the Chinese press between 2001 and 2010 and that turned out to be false showed that half of the news stories attributed information to only anonymous sources (Zhang, 2011). Pjesivac and Rui (2014) found that people in the United States and China rated news stories with named sources as more credible than those stories that had only anonymous sources to provide news. Li (1998) carried out a content-analysis of the sources used in The New York Times' coverage of China.…”
Section: Literature Reviewmentioning
confidence: 98%
“…On the other hand, some scholars posited that an anonymous source would be perceived as less credible than an identified source under such situations as news storytelling (Pjesivac & Rui, 2014), high-quality stories (Sternadori & Thorson, 2009), and computer-mediated group communication (Rains, 2007b). A possible explanation is that message senders are expected to follow the cultural and societal norm of identifying themselves while sending out their messages (Forman, Ghose, & Wiesenfeld, 2008;Rains, 2007a); thereby, if they go against the norm by concealing their identities, it is probably because they do not want to be held accountable for their contributions (Rains, 2007b) and their words are thus regarded as less credible.…”
Section: Anonymitymentioning
confidence: 99%
“…By providing a measure of protection, anonymity allows message senders to deliver their messages without the consequence of having the information attributed to them (Rains, 2007a). Previous studies have examined how anonymity affects message credibility and persuasiveness, but drawn inconsistent conclusions (Chesney & Su, 2010; Pjesivac & Rui, 2014; Rains, 2007a; Sternadori & Thorson, 2009).…”
Section: Anonymitymentioning
confidence: 99%